Beyond the Scholl reaction – one-step planarization and edge chlorination of nanographenes by mechanochemistry. Issue 60 (25th November 2021) - Baier, Daniel M.; Grätz, Sven; Jahromi, Babak Farhadi; Hellmann, Sarah; Bergheim, Konrad; Pickhardt, Wilm; Schmid, Rochus; Borchardt, Lars
Abstract : The edge chlorination of the benchmark nanographenes triphenylene and hexa- peri -hexabenzocoronene is conducted mechanochemically. Planarization and edge chlorination are combined which allows the preparation of chlorinated nanographenes in one step. Abstract : The edge chlorination of the benchmark nanographenes triphenylene and hexa- peri -hexabenzocoronene is conducted mechanochemically. This approach overcomes solubility limitations and eliminates the need for elaborate chlorination conditions. Additionally, the planarization of oligophenylenes and their edge-chlorination can be combined in a one-pot approach requiring as little as 60 minutes.